Early detection of difficulties in reading learning in chilean children of four years old - Ramírez Balmaceda, Ana Karen (2022)
The objective of the research was to validate an early detection test for reading difficulties (Cuetos and Suárez-Coalla) in a sample of four-year-old Chilean children. The test includes six tasks that assess the components of phonological processing: a) Phoneme discrimination with five pairs of words for children to recognize if it sounds the same or different; b) Identification of phonemes, a sound is presented and the child repeats it and then recognizes if that sound is in other words; c) Segmentation of syllables, each syllable of a word is identified; d) Repetition of pseudowords, the child repeats words that do not exist because they have been invented; e) Repeating digits of different sizes without making mistakes, the series ranges from one to five digits; f) Verbal fluency, the name of an animal is presented and the child must repeat all the animals that occur to him, in a limited time. The results confirm that the test is acceptable in terms of structure and components of phonological awareness (identification and discrimination of phonemes, syllable segmentation, repetition of digits and pseudowords, verbal fluency) as predictors of reading. The statistical indicators of validity and reliability were very similar in the Spanish and Chilean samples. The linguistic aspects, such as the wording of the instructions and the statements of the items, did not need to be modified. This was reported by the therapists who applied the test to children in the various educational centers; and the systematic observation of the investigators confirms that the task was carried out without any significant difficulties.